Development and validation of UV spectrophotometric method for simultaneous estimation of nitrate and nitrite in water, soil, drug and vegetable samples - Nemade, Kanchan Sudhakar; Attarde, Sanjay (International Journal of Advanced Chemistry, 2014)
A sensitive and specific spectrophotometric method has been developed for the simultaneous determination of nitrate and nitrite at trace levels. The proposed method is based on diazotization of nitrite with a pharmaceutical compound-metoclopramide (4-amino-5-chloro-N-(2-(diethylamino)ethyl)- 2-methoxybenzamide) in acid medium to form diazonium ion which is coupled with ethyl acetoacetate (EAA) in basic medium to form azo dye, showing absorption maxima at 437.5 nm. Different variables affecting the reactions are optimized. The method is precise and accurate and has been applied to water, soil, drug and vegetable samples. The results of the investigated method using metoclopramide were compared with available official literature method. The results obtained by the proposed method agree well with the standard established method. Keywords: Diazotization, Nitrate and Nitrite, Spectrophotometric Estimation.